Pengaruh Komunikasi Interpersonal terhadap Kinerja Karyawan SiCepat Ekspres - Putri, Azzahra Amelia; Ramdan, Ahmad Taufiq Maulana; Recky (LITERAKOM: Jurnal Literasi dan Komunikasi, 2025)
This study aims to investigate the relationship between interpersonal communication indicators and employee performance at SiCepat Ekspres Bandung Sumberasih. The first survey's findings indicated that issues existed with interpersonal communication indicators, such as a lack of transparency between subordinates and superiors and a lack of support between superiors and coworkers. This research employs a quantitative descriptive methodology. The two kinds of data employed in this study are primary and secondary. Secondary data is gathered from publications and other sources of information pertaining to the research topic, whereas primary data is derived from the answers to questionnaires. The purpose of this study is to determine the partial and simultaneous effects of the independent and bound variables. The study's conclusions demonstrate that interpersonal communication significantly and favorably affects worker performance at the same time.